2005
DOI: 10.1016/j.visres.2005.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Attention modulates psychophysical and electrophysiological response to visual texture segmentation in humans

Abstract: To investigate whether processing underlying texture segmentation is limited when texture is not attended, we measured orientation discrimination accuracy and visual evoked potentials (VEPs) while a texture bar was cyclically alternated with a uniform texture, either attended or not. Orientation discrimination was maximum when the bar was explicitly attended, above threshold when implicitly attended, and fell to just chance when unattended, suggesting that orientation discrimination based on grouping of elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
6
31
0
Order By: Relevance
“…We here found an enhancement of the EEG activity around the occipital region for target compared to reference GRF stimuli. A number of studies using EEG, MEG and fMRI have demonstrated neural correlates of figure-ground segmentation (Appelbaum et al, 2006;Caputo and Casco, 1999;Casco et al, 2005;Doniger et al, 2000;Grill-Spector et al, 1998;Halgren et al, 2003;Kastner et al, 2000;Murray et al, 2004Murray et al, , 2002Schira et al, 2004;Schubo et al, 2001;Sehatpour et al, 2006), as well as single-neuron recordings in animals (Lamme, 1995;Polat et al, 1998;Sagi, 1993, 1994;Zhou et al, 2000;Zipser et al, 1996). These studies have suggested the involvement of V1, V2, the lateral occipital cortex (LOC) and V4, supporting the present findings.…”
Section: Neurophysiological Correlate Of Feature Synergysupporting
confidence: 88%
See 1 more Smart Citation
“…We here found an enhancement of the EEG activity around the occipital region for target compared to reference GRF stimuli. A number of studies using EEG, MEG and fMRI have demonstrated neural correlates of figure-ground segmentation (Appelbaum et al, 2006;Caputo and Casco, 1999;Casco et al, 2005;Doniger et al, 2000;Grill-Spector et al, 1998;Halgren et al, 2003;Kastner et al, 2000;Murray et al, 2004Murray et al, , 2002Schira et al, 2004;Schubo et al, 2001;Sehatpour et al, 2006), as well as single-neuron recordings in animals (Lamme, 1995;Polat et al, 1998;Sagi, 1993, 1994;Zhou et al, 2000;Zipser et al, 1996). These studies have suggested the involvement of V1, V2, the lateral occipital cortex (LOC) and V4, supporting the present findings.…”
Section: Neurophysiological Correlate Of Feature Synergysupporting
confidence: 88%
“…This contour-specific negative deflection resembles a negative shift observed at occipital electrodes for both single-and double-feature target GRF stimuli in experiments 2 and 3 of the present study, regarding latency, spatial distribution, and experimental conditions where these were elicited. The contourspecific negative deflection also resembles the texture segregation visual-evoked potential (tsVEP), which has been observed at occipital electrodes (Bach and Meigen, 1997;Bach et al, 2000;Casco et al, 2005;Fahle et al, 2003;Romani et al, 2003). In contrast, the longlasting negative deflection we observed was found locally at an inferior temporal electrode when synergy was observed by presenting two features simultaneously.…”
Section: Comparison With Similar Erp Componentssupporting
confidence: 69%
“…Our analysis thus has provided the first direct evidence that figure and background regions activate distinct cortical networks. In previous EEG studies that used texture-defined forms (Caputo and Casco, 1999;Schubo et al, 2001;Romani et al, 2003;Casco et al, 2005), figure/background processing was studied by subtracting responses to segmented stimuli from those of uniform stimuli. This procedure effectively eliminates background-related activity and focuses the analysis on figure-related responses and nonlinear figure/background interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Memory, attention, language, visuospatial functions, all certainly will have some degree of impairment in when most basic functions are impaired [197][198][199][200][201][202][203][204]. Although there are processing in parallel, in those cases, the hierarchical processing is much stronger and influencer.…”
Section: Future Perspectivesmentioning
confidence: 99%